The Early Preventive Effort of Narcotic Abuse at Senior High School (SMA) in Aceh Besar and Sabang (A Study According to Islamic Law) - Muhammad Jamal, Irwansyah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
Efforts to prevent narcotics abuse, especially for teenagers, are very necessary. bearing in mind the conditions in Indonesian society, the use of narcotics is not only committed by adults, but it’s also practiced by teenagers who are schooling. Thus, protecting young people who are still in school-age becomes an obligation that cannot be abandoned, both individuals and society. On the one hand, a lot of thoughts and efforts have been made related to the prevention of narcotics, starting from the national program that forms a special agency to deal with narcotics (National Narcotics Agency) to non-governmental organizations. However, narcotics abuse still occurs in the community, including among students. Therefore, preventive action is needed to break narcotics abuse, especially in the school environment. The High Schools in Aceh, especially Aceh Besar and Sabang, have made some efforts, such as a. urine test; b. counseling/guidance and c. school rules and regulations. These efforts have had a positive impact on students. However, environmental conditions may influence them to trap in narcotics abuse, in case if the control from the various community is not done. These prevention efforts, according to Islamic law are part of amar ma'ruf nahi mungkar.